Problems of the Ecological System in Russia and Directions for Their Solution Based on Economic and Social Development Programs - POLTARYKHIN, Andrey; NOSOV, Vladimir; POLETAEVA, Larisa; AVDOTIN, Vladimir; GRISHIN, Viktor; BABAKISIYEV, Manaf (Journal of Environmental Management and Tourism, 2019)
The article deals with the problems of the ecological system in Russia and the directions of their solution on the basis of economic and social development programs. Consumer attitudes of people to the environment is the main cause of the deterioration of its condition, which leads to a decrease in stocks of non-renewable natural resources. In addition, it threatens the existence of humanity. The environmental problems of our time require not only the introduction of resource-saving technologies in all sectors of production, the use of alternative energy sources, but also ensuring the restoration of the already damaged ecosystem resilience and their preservation in the future.